PENERAPAN TEKNOLOGI INSEMINASI BUATANPADA TERNAK DOMBA - Nur Rasminati, Setyo Utomo dan (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2012)
The application of AI technology was aimed to improve the qualityof sheep in the village Tanjungharjo within the framework of communityeconomic empowerment. The activities centered in the hamlet Klajuran andTanjunggunung, which has biggest number of sheep population. Thisactivity was began with the selection of candidates for ewes and superiormales. 32 ewes and 2 males were used in this activity. Prior to the AI, theewes synchronized using PGF2Î± with a dose of 0.2 and 0.5 ml / IM / headand part of the ewes fed flushing. The results showed that thesynchronization of applied technology for both flushing and non flushingindicate the occurrence of estrus with estrous intensity the average of 2.8. Itcould be concluded that almost all ewes synchronized shows estrous withnear maximal intensity (3), which is swollen, red and slimy. Analysis ofvariance of flushing treatment showed significant different to estrousintensity (3 vs 2.6). Synchronization using different doses of PGF2Î±treatment and flushing yielded an average pregnancy rate is different too.The average pregnancy in the treatment flushing was 100%, while the nonflushingwas 70%. While for the treatment of PGF2Î± dose, to 0.5 ml / headpregnancy rate reached 95% and to 0.2 ml / head pregnancy rate reached80%. It can be concluded that the flushing and different doses of PGF2Î±have effect on the intensity of estrus and achievements AI.